Single versus Double Burr Holes for Treating Chronic Subdural Hematoma - Khan, Uzzal Kumer Sadhu; Sarker, Asit Chandra; Morshed, Md Mahamudul Haq; Hasan, Md Motasimul; Hoque, Saiful; Hawlader, Md Riaz Ahmmed; Islam, Md Rakibul (Bangladesh Journal of Neurosurgery, 2020)
A subdural hematoma is a collection of blood below the inner layer of the dura but external to the bran and arachnoid membrane.Chronic subdural hematoma is commonly associated with cerebral atrophy, occur in the elderly after apparently insignificant head trauma. The incidence of Chronic subdural hematoma increases with age and after 70 years of age. Surgical evacuation of hematoma is indicated in patients who are clinically deteriorate or do not improve. Surgery can bring a rapid clinical improvement with a favorable outcome in over 80% of patient. Methods: This study was a prospective intervention study. Results: It was observed that 29 (96.6%) patients were alive in group A and 27 (90.0%) patients alive in group B in GOS scoring on the 7th POD. The alive patients were again divided into 4 sub groups, as shown in the table. Among total 60 patients, in Group A 1(3.4%) died and 3 (10.0%) died in Group B. After 3 months follow up, it was observed that 29 (96.6%) patients were alive in group A and 27 (90.0%) patients alive in group B. The alive patients were again divided into 4 sub groups, as shown in the table. Persistent vegetative and severe disability was not improved in Group B. Conclusion: In my study it was observed that the surgical outcome in single burr hole craniotomy is better than double burr hole craniotomy for treating of chronic subdural hematoma. Bang. J Neurosurgery 2020; 9(2): 99-104